Job Creation Versus Labor Rights: A Justice-Theoretical Analysis of Indonesia's Omnibus Law Through Khadurian Ethics and Rawlsian Social Contract Theory - M. Aldawsari, Mohammed Abdullah M. Aldawsari; Jannah, Nur Miftahul; Abdi, Mukhlis; Alam, Zidan Syamsul; Lim, Sakinas (JURNAL INDO-ISLAMIKA, 2025)
Indonesia’s Omnibus Law on Job Creation (Law No. 6/2023) sparks debate over labor rights, balancing economic growth and social justice. This study analyzes the law through John Rawls’ and Madjid Khadduri’s justice theories using normative-philosophical methods. Examination of legislative texts and policy documents reveals normative conflicts: severance pay cuts, flexible contracts, and unionization limits violate Rawls’ difference principle, disproportionately harming vulnerable workers. Khadduri’s Islamic justice framework further identifies breaches of maqāṣid al-sharīʿah, particularly eroding worker dignity (ḥifẓ al-ʿird) and collective welfare (maṣlaḥah). The study advocates labor policies integrating universal ethics—merging market efficiency with moral obligations—to protect workers. By synthesizing Rawlsian liberalism and Islamic ethics, it proposes a cross-cultural justice model for pluralistic societies. Findings emphasize reconciling legal reforms with transcendental values, ensuring labor protections align with both human rights and religious norms. This framework addresses Indonesia’s policy tensions while offering a template for equitable labor governance in culturally diverse contexts.